2018
DOI: 10.1186/s12909-017-1114-x
|View full text |Cite|
|
Sign up to set email alerts
|

Psychosocial issues discovered through reflective group dialogue between medical students

Abstract: BackgroundThe biopsychosocial model is a comprehensive approach emphasizing holistic medical care. However, medical curricula that incorporate narrative reflective writing and group dynamic discussion of psychosocial issues among patients and their family members in reflective dialogue groups are currently underutilized. The aim of this study was to determine psychosocial issues among patients and their family members through medical students’ reflective dialogue groups.MethodsThis study was completed as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Regression analyses revealed that working years is significant predictive factors for medical personnel's KAP. Longer working years predicts better knowledge, more positive attitude, and better practice, which is always accompanied by greater experience of listening to patients' stories, greater interaction with patients (and with a wider range of patients), and greater internalization of the relationship competencies learned in clinical practice [ 19 , 20 ]. Moreover, younger doctors generally have a greater economic pressure to support their families out of their medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analyses revealed that working years is significant predictive factors for medical personnel's KAP. Longer working years predicts better knowledge, more positive attitude, and better practice, which is always accompanied by greater experience of listening to patients' stories, greater interaction with patients (and with a wider range of patients), and greater internalization of the relationship competencies learned in clinical practice [ 19 , 20 ]. Moreover, younger doctors generally have a greater economic pressure to support their families out of their medical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Reflective practice is an important skill for all clinicians [10], although most evidence for its role in undergraduate medical education comes from high-income country (HIC) settings rather than low-and middle-income countries (LMICs) [11]. Reflective practice-based approaches to medical undergraduate training have recently been reported in diverse settings, from Taiwan [12,13] to Thailand [14] and South Africa [15]. One American study proposed a tool to measure reflective capacity among medical students [16].…”
Section: Reflective Practicementioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that they had had mistakenly put the wrong IRB number in the last paragraph of the Methods section (as IRB NO. : IRB101–80 instead of IRB102–20 as given in the Ethics approval and consent to participate in Declarations ).…”
Section: Correctionmentioning
confidence: 99%